Jony Ive : the genius behind Apple's greatest products - Kahney, Leander (New York : Portfolio/Penguin, 2013)
"The bestselling author of Inside Steve's Brain profiles Apple's legendary chief designer, Jonathan Ive. Jony Ive's designs have not only made Apple one of the most valuable companies in the world; they've overturned entire industries, from music and mobile phones to PCs and tablets. But for someone who has changed the world as much as he has, little is widely known about Apple's senior vice president of industrial design. Unlike his former boss and creative partner Steve Jobs, Ive shuns the spotlight. Naturally shy and soft-spoken, he lets his work speak for itself and concerns himself only with his craft"--
School days -- A British design education -- Life in London -- Early days at Apple -- Jobs returns to Apple -- A string of hits -- The design studio behind the Iron Curtain -- Design of the iPod -- Manufacturing, materials and other matters -- The iPhone -- The iPad -- Unibody everywhere -- Apple's MVP.
BIBINDX
Keywords: Ive, Jonathan, -- 1967-; Apple Computer, Inc. -- History; Industrial designers -- United States -- Biography; Product design -- United States